Modeling e-learning effectiveness and usability - Leong, Lock Wah. (2009)
For the last two decades, many organizations, junior schools, Universities and educational institutions have been investing in the information technologies to improve education and training at an increasing rate. Especially in the corporate worlds, there is strong push for continuous education and training for their human resources that are critical to an organization’s success. Electronic Learning (E-Learning) has been identified as the key enabler for people and organizations to keep up with changes in the global economy that now occur in the fast Internet time. However, it is also important to note that most E-learning programs exhibit higher dropout rates when compared with traditional instructor-led courses. Therefore, it is important to establish the Effectiveness and Usability evaluation method/model for E-Learning applications.